Awareness of Artificial Intelligence (AI) among Undergraduate Students - Tripathi, Chhabi Ratna (NPRC Journal of Multidisciplinary Research, 2024)
Artificial intelligence (AI) is revolutionizing numerous fields, including higher education, by offering innovative tools and techniques that enhance learning, assessment, and skill development. This research investigates the awareness, perceptions, and competencies of undergraduate students in the Kathmandu Valley concerning AI. The study aims to evaluate students' understanding of AI, identify knowledge gaps, and recommend curriculum enhancements to align education with industry demands. A quantitative research design was employed, collecting data from 123 students across diverse colleges using a structured Likert-scale questionnaire. The findings reveal that while many students recognize AI's potential in streamlining academic tasks and shaping future careers, there are significant gaps in their understanding and practical application of AI technologies. The study highlights the dual nature of AI, which can serve as both an enabler of efficiency and a source of apprehension, particularly concerning job displacement and ethical implications. It also identifies disparities in access to AI tools due to socioeconomic factors, underscoring the importance of addressing the digital divide. The research concludes that integrating AI-related content into higher education curricula is critical for preparing students for an AI-driven workforce. By fostering AI literacy, ethical awareness, and hands-on skills, institutions can empower students to leverage AI responsibly and effectively. The novelty of this study lies in its context-specific approach, exploring AI's impacts on undergraduate education in a developing region, and providing actionable insights for curriculum development and policy-making in the age of AI.